2023
DOI: 10.3389/fnbeh.2023.957203
|View full text |Cite
|
Sign up to set email alerts
|

Is DNA methylation in the brain a mechanism of alcohol use disorder?

Abstract: Alcohol use disorder (AUD) is a worldwide problem. Unfortunately, the molecular mechanisms of alcohol misuse are still poorly understood, therefore successful therapeutic approaches are limited. Accumulating data indicate that the tendency for compulsive alcohol use is inherited, suggesting a genetic background as an important factor. However, the probability to develop AUD is also affected by life experience and environmental factors. Therefore, the epigenetic modifications that are altered over lifetime like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Similar over-represented gene ontology categories were also found to be differentially regulated following binge ethanol in the PFC of adolescent DBA/2J mice in prior studies ( Wolstenholme et al, 2017 ; Brocato and Wolstenholme, 2023 ). Epigenetic regulation through histone demethylase activity is particularly intriguing as a growing number of studies show ethanol alters methylation marks ( Bohnsack and Pandey, 2021 ; Brocato and Wolstenholme, 2021 ; Siomek-Gorecka et al, 2021 ; Jarczak et al, 2023 ) and inhibits the production of methyl substrates ( Watson et al, 2011 ; Brocato and Wolstenholme, 2021 ; Jarczak et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar over-represented gene ontology categories were also found to be differentially regulated following binge ethanol in the PFC of adolescent DBA/2J mice in prior studies ( Wolstenholme et al, 2017 ; Brocato and Wolstenholme, 2023 ). Epigenetic regulation through histone demethylase activity is particularly intriguing as a growing number of studies show ethanol alters methylation marks ( Bohnsack and Pandey, 2021 ; Brocato and Wolstenholme, 2021 ; Siomek-Gorecka et al, 2021 ; Jarczak et al, 2023 ) and inhibits the production of methyl substrates ( Watson et al, 2011 ; Brocato and Wolstenholme, 2021 ; Jarczak et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation (DNAm) is an epigenetic mark that contributes to modulation of gene expression by modifying the accessibility of transcription factors to chromatin. Alterations in DNAm are reported in heavy drinking humans, monkeys and rodents 3 5 , 35 , 36 , and a recent study demonstrated that knockdown of DNA methyltransferases reduced Kcnn3 expression and increased intrinsic excitability of cultured cortical neurons 37 . Thus, we measured DNAm levels at a differentially methylated region in exon 1 (MR-ex1) that coincides with a cross-species regulatory region within the KCNN3 promoter.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation (DNAm) is an epigenetic mark that contributes to the modulation of gene expression by modifying the accessibility of transcription factors to chromatin. Alterations in DNAm are reported in heavy-drinking humans, monkeys and rodents [ 3 5 , 35 , 36 ], and a recent study demonstrated that knockdown of DNA methyltransferases reduced Kcnn3 expression and increased intrinsic excitability of cultured cortical neurons [ 37 ]. Thus, we measured DNAm levels at a differentially methylated region (DMR) in exon 1 (MR-ex1) that coincides with a cross-species regulatory region within the KCNN3 promoter.…”
Section: Introductionmentioning
confidence: 99%